Signals & systems: with matlab programs - Sharma, Sanjay (S.K. Kataria & sons, 2006)
Signals & systems: with matlab programs / Sharma, Sanjay. -- New Delhi: S.K. Kataria & sons, 2006 621.3822 Sh531e5 5th ed. No. of Copies : 1